2017
DOI: 10.7764/rcia.v44i1.1653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crop load on the phenological, vegetative and reproductive behavior of the ‘Frantoio’ olive tree (Olea europaea L.)

Abstract: V. Beyá-Marshall, and T. Fichet. 2017. Effect of crop load on the phenological, vegetative and reproductive behavior of the 'Frantoio' olive tree (Olea europaea L.). Cien. Inv. Agr. 44(1): 43-53. The aim of this study was to characterize the phenological, vegetative and reproductive behavior variables of 'Frantoio' olive trees in an "off" year (with a low crop load) and an "on" year (with a high crop load). To do this, during the 2011-2012 and 2012-2013 seasons, "off" and "on", respectively, phenological varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…However, the interannual variability in thermal and rainfall regimes (Vaughan et al, 2017) affects regular production. Fruit and oil yields obtained were similar to those obtained in traditional Mediterranean basin regions (García et al, 2013; Gispert et al, 2013; Rallo et al, 2013; Díez et al, 2016; Marino et al, 2017) as well as in new olive growing regions (Tapia et al, 2009; Trentacoste et al, 2015; Beyá-Marshall and Fichet, 2017).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, the interannual variability in thermal and rainfall regimes (Vaughan et al, 2017) affects regular production. Fruit and oil yields obtained were similar to those obtained in traditional Mediterranean basin regions (García et al, 2013; Gispert et al, 2013; Rallo et al, 2013; Díez et al, 2016; Marino et al, 2017) as well as in new olive growing regions (Tapia et al, 2009; Trentacoste et al, 2015; Beyá-Marshall and Fichet, 2017).…”
Section: Discussionsupporting
confidence: 76%
“…After several years, the average and the overlap flowering period can be identified among cultivars in relation to climatic characteristics (Orlandi et al, 2005; Benlloch-González et al, 2018). Negative climatic events in non-traditional producing regions as Argentina and Chile, can result in null harvest, leading to regional alternate bearing processes (Cuevas et al, 1994; Goldschmidt, 2005; Beyá-Marshall and Fichet, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On a weekly basis and randomly (we crossed the field following the letter W to collect the fruits), we collected and examined 6 fruits per zone trap (we had 49 zone traps) up to September 22 (total of 250 fruits); after this date, we collected 12 fruits per zone trap (total of 588 fruits) to obtain more representative samplings, given that the rate of infestation would be increased, and the fruits were collected in three separate bags related to the three fruit load rates obtained and numbered according to the three zone traps: 1 = 50-75%, 2 = 25-50%, and 3 = 0-25%. The calculation of these rates was in relation to the scale of fruit production [26,[30][31][32][33].…”
Section: Rate Of Fruit Infestation Rfimentioning
confidence: 99%
“…The size gain of the olive fruits was related to the percentage of the fruit load rate (Table 2). Many studies have shown the effect of the fruit load rate, the age, and the variety on the fruit size [31][32][33].…”
Section: Bbch and Fruit Dimensionsmentioning
confidence: 99%
“…Studies reported many factors which could affect pistil abortion such as genetic factor, Alagna et al (2016) reported many genes involved in pistil abortion of olive such as BAM 1, Inv-cw, Inv-V and GBSSI which involve in starch and sucrose metabolism and NLP1, SPDS and ADC which involve in polyamines biosynthesis. In addition, environmental conditions like drought, mineral deficiency and previous year yield could affect flower gender in olive (Rapoport et al, 2012;Rosati et al, 2012;Beya-Marshall and Fichet, 2017). Garcia-Mozo et al (2009) mentioned that phenological data is an important and sensitive tool in evaluating the adaptability of plants in local environments and how those plants respond to climate change.…”
Section: Introductionmentioning
confidence: 99%